Reseña de F. Capek, Archaeology, History, and Identity Formation of Ancient Israel - Jaruf, Pablo (Revista Bíblica, 2025)
F. Capek, Archaeology, History, and Identity Formation of Ancient Israel, Karolinum Press, Prague 2024(2018), 256 pp. ISBN 978-80-246-5417-1 / ISBN PDF 978-80-246-5525-3 / ISBN EPUB 978-80-246-5526-0.